Gemcitabine nanoparticles promote antitumor immunity against melanoma. (January 2019) - Zhang, Yuan; Bush, Xin; Yan, Bingfang; Chen, Justin A.
Abstract: Myeloid-derived suppressor cells (MDSCs) promote tumor-mediated immunosuppression and cancer progression. Gemcitabine (Gem) is a MDSC-depleting chemotherapeutic agent; however, its clinical use is hampered by its drug resistance and inefficient in vivo delivery. Here we describe a strategy to formulate a Gem analogue gemcitabine monophosphate (GMP) into a lipid-coated calcium phosphate (LCP) nanoparticle, and investigate its antitumor immunity and therapeutic effects after systemic administrations. In the syngeneic mouse model of B16F10 melanoma, compared with free Gem, the LCP-formulated GMP (LCP-GMP) significantly induced apoptosis and reduced immunosuppression in the tumor microenvironment (TME). LCP-GMP effectively depleted MDSCs and regulatory T cells, and skewed macrophage polarization towards the antitumor M1 phenotype in the TME, leading to enhanced CD8 + T-cell immune response and profound tumor growth inhibition. Thus, engineering the in vivo delivery of MDSC-depleting agents using nanotechnology could substantially modulate immunosuppressive TME and boost T-cell immune response for enhanced antitumor efficacy.